Wayang Sasak As A Media For Dakwah Case Study Of Ki Dalang Buwana Sanggar H. Safwan, Ar In Batu Rimpang Dusun Badrain Village Narmada District, West Lombok Regency - Sauri , Sopiyan; Kurnia, Wahyu; Permana, Beny; Junaidi, Junaidi; Subhan, Subhan; Taufiqqurrahman (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2025)
Shadow puppets is one of the most prominent highlights of Indonesian culture among other cultural. Puppets culture include acting, sound, music, literature, sculpture and symbolism. Puppets as a point of Sasak and Islamic cultural values is a very valuable momentum for the development of Sasak cultural treasures. Puppets for Sasak people are not only entertainment, but also a communication tool that can connect the will of the puppeteer through the storyline, so that dakwah can be embedded in a Sasak puppet performance. Based on this, the purpose of this study is to answer the question of how a puppeteer packages the delivery of messages (Dakwah) in puppet shows, especially in Sanggar Buwana Ki Dalang H. Safwan, AR, in Batu Rimpang, Badrain Village, Narmada District, West Lombok Regency. The methodology used is descriptive qualitative approach. Researchers do and try to collect, process and analyze qualitatively and embodied in the concept. While the data obtained by the researcher by means of observation, interviews, study documentation. The results of the research are the efforts of puppeteers in inserting dakwah messages in puppet shows, the approach in inserting dakwah messages through puppet media, has advantages that can be directly benefited by the community until now. In the staging or performance of puppets, it has a lot of influence on its fans. Because in the staging or performance of puppets contains a lot of philosophy of life and noble values. For the inhibiting factors in the process of puppet performances in carrying out the insertion of dakwah messages are the lack of publication to be spread outside the village so that the audience from outside the village is small, limited funding from the committee so that the puppeteer cannot add personnel which is one of the allures to attract the attention of the audience to watch until completion, and the love of puppets which is starting to decline, especially for the younger generation.